Modelo de gestión para el desarrollo territorial sostenible del turismo en Manabí, Ecuador - Barre Ormaza, Jipson Leonel (2019)
This research aims to design a management model for the sustainable territorial development of tourism in Manabí. It is a mixed investigation that uses a descriptive - exploratory approach based on a methodology composed of three phases and begins with the tourist diagnosis that, through instruments such as surveys, interviews, document review and SWOT matrix, allowed to identify the problems and the causes that limit tourism development in the province, giving as main problem the absence of a management model that contributes to the sustainable territorial development of tourism in the province of Manabí. In the second phase, a market analysis was carried out on the supply of products and services, tourist demand was segmented through multivariate statistical analyzes such as factor analysis and analysis by k-media conglomerates. A closed and open questionnaire processed by the statistical package SPSS version 21 was applied as an instrument, as the next step; through interviews with officials of the tourism departments of Manabí, the planning processes, territorial planning and the level of commitment that they allocate towards entrepreneurs in relation to tourism were verified. In the third and final phase as a proposal under study, a tourism management model was established in which its objectives, mission, vision, values were established; marketing strategies were established that allow Manabí to be positioned as a tourist destination of interest. In order to obtain sustainable management and solve detected problems.